2015
DOI: 10.1515/aoas-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships Among Linear Type Traits and Milk Production Traits of Holstein Dairy Cattle

Abstract: The breeding goal in dairy cattle is to increase lifetime profit per animal. Profit is a function of production and the time that a cow remains in herd. Thus, profit can only be recorded when a cow is culled, and breeding value of more profitable aniUnauthenticated Download Date | 5/13/18 1:11 AM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
22
2
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 35 publications
14
22
2
11
Order By: Relevance
“…The factors cited above as an explanation for the difference between the heritability estimates for FL1 and FL2 may also explain why the genetic correlation between FL1 and FL2 was not stronger. The results of genetic correlations were similar to those observed in previously published studies in dairy cattle (Berry et al, 2004;Bohlouli et al, 2015). Bohlouli et al (2015) reported genetic correlations between rear leg rear view and foot angle of -0.67, and between rear leg rear view and rear leg side view of -0.11.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The factors cited above as an explanation for the difference between the heritability estimates for FL1 and FL2 may also explain why the genetic correlation between FL1 and FL2 was not stronger. The results of genetic correlations were similar to those observed in previously published studies in dairy cattle (Berry et al, 2004;Bohlouli et al, 2015). Bohlouli et al (2015) reported genetic correlations between rear leg rear view and foot angle of -0.67, and between rear leg rear view and rear leg side view of -0.11.…”
Section: Resultssupporting
confidence: 90%
“…The results of genetic correlations were similar to those observed in previously published studies in dairy cattle (Berry et al, 2004;Bohlouli et al, 2015). Bohlouli et al (2015) reported genetic correlations between rear leg rear view and foot angle of -0.67, and between rear leg rear view and rear leg side view of -0.11. The greatest absolute value has been reported by Berry et al (2004), who obtained a genetic correlation of -0.88 between leg position and hoof angle.…”
Section: Resultssupporting
confidence: 90%
“…Most udder traits had low heritabilities except for teat length (0.36). The heritability values of most udder traits were similar to previously published studies (Mrode and Swanson, 1994;Veerkamp and Brotherstone 1997;Vollema and Groen, 1997;Toghiani, 2011;Bohlouli et al, 2015;Viegas et al, 2015;Prestes et al, 2017).…”
Section: Resultssupporting
confidence: 88%
“…Está compuesta por agua, grasa, proteína, lactosa y minerales (Walstra, Wouters, & Geurts, 2006). Estos componentes varían según el patrón racial de los animales (DePeters, Medrano, & Reed, 1995), las condiciones climáticas en donde se desarrolla el sistema de producción (WingChing-Jones & Mora-Chaves, 2015), el estado sanitario de la ubre (Alhussien & Dang, 2018), el número de lactancia (Bohlouli, Alijani, & Varposhti, 2015), el contenido de almidones (Gao & Oba, 2016), el balance catión anión (Iwaniuk & Erdman, 2015) y el contenido de proteína en la dieta (Sinclair, Garnsworthy, Mann, & Sinclair, 2014); la edad del animal (Bohlouli et al, 2015), el estado de lactancia (Bohlouli et al, 2015) y los litros producidos al día (Feltes et al, 2016) entre otras variables.…”
unclassified